PEMANFAATAN METODE BIAYA VOLUME LABA SEBAGAI ALAT BANTU PERENCANAAN LABA PADA TAHU BAXO IBU PUDJI TAHUN 2017 - Frizka Dhika Aprilianti; Hartono - (Politeknik Negeri Semarang, 2019)
The purpose of this research are to calculate the profit planning of TahuBaxoIbuPudjiin 2017 and the influence of cost mutation to profit mutation. Analytics cost of profit volume is the equipment that useful for planning and creating a decision especially the relation between cost, volume and profit. Method that used to accumulate the data is interview method and literature review. Whereas the data that used is quantitative in the form selling price, cost data and selling in 2016 then the qualitative data is general description of the company. The writing method used is description method and exposition method. The final calculation used cost profit volume method is shown that planning of profit for 2017 is Rp 244.811.327 with sales of boiled Tahubaxo is 1.065.451 units and 451.637 units of fried Tahubaxo. Decreasing of sales income 6% will affected loss Rp 60.991.902 and increasing of sales price 6% will gain profit from Rp 244.811.166 to Rp 550.614.234. Mutation of variabel cost 5% will affected decreasing of profit fromRp 244.811.327 to Rp 55.679.045 (increase) or increasing become Rp 433.943.287 (decrease). In case of change simultaneously 6% sales price and 5% variable cost will affected profit decrease from Rp 244.811.166 to Rp 128.140.219 (decrease) or increasing become Rp 361.482.113 (increase). Then every change one rupiah of fixed costs will change profit Rp 5,24